Relationship between mediation as a conflict resolution method and corporate social responsibility: a contribution to peace-building and sustainable development - Guerrero-Vega, Roberto N. (2023)
Latin America is one of the most unequal regions on the planet, a condition that favors and consolidates the violent structures adopted by societies that threaten peace and the economic and cultural development of future generations. This article has a qualitative approach, based on a non-experimental design, under a cross-sectional bibliographicdocumentary level. Its general objective is to analyze the relationship between Mediation as a Method of Conflict Resolution (MSC) and Corporate Social Responsibility (CSR), as well as to support how this interaction has contributed to peace building and sustainable development. After the literature review and documentary analysis, the generalities of CSMs were known, as well as the role played by mediation and Social Responsibility according to their scope of action. Based on this analysis, it was concluded that mediation as a CSM is presented as a tool for conflict management and can also be implemented as a public policy for the benefit of CSR, and consequently it was shown that the interaction of both figures represents a significant contribution to peace-building, social welfare and sustainable development.